Antibacterial Activity of New Polyester Diterpenes from Euphorbia guyoniana - A. EL-BASSUONY, ASHRAF (Asian Journal of Chemistry, 2010)
The dichloromethane extract of the aerial parts of Euphorbia guyoniana afforded two new polyesters diterpene, named guyonianin C and D, a rare classes of bicyclic diterpenes. Their structure were established by high-field NMR spectroscopic methods, including DEPT, COSY, NOESY, HMQC and HMBC.